THE ANALYSIS OF FOOD QUALITY AND SERVICE QUALITY OF DUTA CATERING TOWARDS CUSTOMER SATISFACTION AND BRAND LOYALTY - ABDILLAH NATA PRASETYA, MUHAMMAD FARHAN; SETYANTO, REFIUS PRADIPTA; AFIF, NUR CHOIRUL (INDONESIAN RESEARCH SOCIETY, 2018)
The study entitled